Internment: The Impact of Internment on Issei and Nisei's Identity in Philip Kan Gotanda's Sisters Matsumoto - Kamel Muthana, Rajiha (Al-Adab Journal, 2019)
During World War II, more than 110 000 Japanese Americans including those Americans of Japanese roots were forced into interior camps after Japanese attack on Pearl Harbor. This experience left indelible scars on the Japanese Americans.